Assessing leadership in junior resident physicians: using a new multisource feedback tool to measure Learning by Evaluation from All-inclusive 360 Degree Engagement of Residents (LEADER). Issue 4 (7th December 2020) - Bharwani, Aleem; Swystun, Dana; Oddone Paolucci, Elizabeth; Ball, Chad G; Mack, Lloyd A; Kassam, Aliya
Abstract : Background: The multifaceted nature of leadership as a construct has implications for measuring leadership as a competency in junior residents in healthcare settings. In Canada, the Royal College of Physicians and Surgeons of Canada's CanMEDS physician competency framework includes the Leader role calling for resident physicians to demonstrate collaborative leadership and management within the healthcare system. The purpose of this study was to explore the construct of leadership in junior resident physicians using a new multisource feedback tool. Methods: To develop and test the Learning by Evaluation from All-Inclusive 360 Degree Engagement of Residents (LEADER) Questionnaire, we used both qualitative and quantitative research methods in a multiphase study. Multiple assessors including peer residents, attending physicians, nurses, patients/family members and allied healthcare providers as well as residents' own self-assessments were gathered in healthcare settings across three residency programmes: internal medicine, general surgery and paediatrics. Data from the LEADER were analysed then triangulated using a convergent-parallel mixed-methods study design. Results: There were 230 assessments completed for 27 residents. Based on key concepts of the Leader role, two subscales emerged: (1) Personal leadership skills subscale (Cronbach's alpha=0.81) and (2) Physicians as active participant-architects within the healthcare system (abbreviated to active participant-architects subscale, Cronbach's alpha=0.78). There were seven main themes elicited from the qualitative data which were analogous to the five remaining intrinsic CanMEDS roles. The remaining two themes were related to (1) personal attributes unique to the junior resident and (2) skills related to management and administration. Conclusions: For healthcare organisations that aspire to be proactive rather than reactive, we make three recommendations to develop leadership competence in junior physicians: (1) teach and assess leadership early in training, (2) empower patients to lead and transform training and care by evaluating doctors, (3) activate frontline care providers to be leaders by embracing patient and team feedback.